The settlement issue in Turkey and the Kurds : an analysis of spatial policies, modernity and war - Jongerden, Joost. (Social, economic, and political studies of the Middle East and Asia, 2007)
In seeking to understand village evacuation in the Kurdistan region of Turkey in the 1980s and 1990s, this book focuses on the spatial aspects of the armed conflict. It tries to explain how settlement and resettlement policies and practices in Turkey have been part of a larger project of political and cultural engineering, based on a revision of a classical understanding of modernity as reflected in the work of Durkheim, Mauss, and Tönnies. This interdisciplinary perspective has allowed contributions from sociology to the political sciences and from history to social geography.